Green plantings in boulevards of Ufa - Konashova S. I., Gulieva E. A. (Interactive science, 2018)
in the article the features of planning and landscaping Ufa boulevards, in a large part impacting on aesthetic level of the urban development are considered. Species composition and quality of green spaces, features of landscape planning are explored in the new sector of the city. It allowed to develop more acceptable options for changing its development pattern and species composition.
Keywords: эстетичность; город; видовой состав; зеленые насаждения; composition; species; бульвар; жизнеустойчивость; boulevard; city; green spaces; aesthetics; resilence